Interferência de adjuvantes e horários de aplicação no espectro de gotas e no desempenho de fungicidas em soja - Colpo, Tiago Lovato (2022)
After reaching the soybean crop [Glycine max (L.) Merrill] the spores of the fungus that causes soybean Asian rust (Phakopsora pachyrhizi) need optimal temperatures and humidity to initiate the infectious process, conditions that occur in the lower strata of the plants with the crop interrow closure. This leaf barrier becomes a problem, as fungicides have low translocation in plants, requiring greater coverage of the crop canopy by spraying the fungicide solution to increase the chances of controlling the pathogen. To this objective, the application rate per hectare can be increased, which reduces the operational efficiency of the applications, or the droplet spectrum used in spraying can be reduced. This reduction, however, implies an increase in the risk of drift, as fine or very fine droplets are more likely to not settle on the target when dragged by the wind or evaporate before reaching the plants. Even more, throughout the day, high temperature, low relative humidity and the occurrence of wind limit the spray window as they are harmful conditions for deposition. Thus, the use of adjuvants appears as an alternative because, according to the manufacturers, these products reduce the phenomenon of drift and the effect of unfavorable environmental conditions for spraying, increasing the application window, in addition to improving the spreadability of the drops on the target, for reduce the surface tension of the spray solution. Therefore, the objective of this work was to evaluate the effect of these products on the physicochemical characteristics of fungicide solutions, the interference of spraying times on the deposition of droplets on the target and the control of soybean Asian rust. For this, studies were carried out under field conditions in the municipalities of Santa Maria-RS, Lagoa dos Três Cantos-RS and Júlio de Castilhos-RS and under laboratory conditions in Santa Maria-RS and Santo Antônio de Posse-SP. In the laboratory, the effect of the addition of adjuvants on surface tension, pH, dynamic viscosity and droplet spectra of fungicides sprays was evaluated. In the field, the response of sprays with different adjuvants was evaluated in the control of soybean Asian Rust, in the crop yield and in the spray deposition for different spraying times during the day (7, 10, 13, 16, 19 and 22:00). The results of the study showed that the addition of adjuvants reduced the surface tension of the fungicidal solutions, while the changes in pH and dynamic viscosity are little evident or null. The effects of adjuvants in the spraying of fungicidal solutions depend on the interaction of the products added in the solutions with the nozzle model used in the operation. The benefits of using alternative adjuvants in combination with recommended adjuvants have not been conclusive. The use of adjuvants in the spray solutions did not increase the deposition in the lower strata of the crop. The best times for the deposition of phytosanitary products in the lower strata of soybean plants are those where the architecture and positioning of the plant leaves favors the penetration of droplets into the canopy, highlighting the times between 10 AM and 01 PM and that the higher deposition rates did not necessarily result in higher yields.